2021
DOI: 10.22266/ijies2021.1031.43
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Students’ Intention to Use E-Learning During Covid-19 Pandemic: A Case Study in Technical College of Management – Baghdad

Abstract: Covid-19 pandemic affected our daily activities. Education is the fastest aspect that has been hindered due to the pandemic. The majority of the schools and universities were prone to global closure. The world turned toward using e-learning as an alternative to traditional learning due to the strict lockdown procedures. This study presents a model to measure the students' intention to use e-learning during the pandemic in Iraq. Technology Acceptance Model (TAM) is utilized with some external variables. Task Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…To ensure that all targeted students have experience dealing with the E-Learning platforms, the data collection process was conducted after 2021, guaranteeing students' experience using E-Learning platforms. In the latter half of 2020, an entire shift in e-learning was implemented in both countries [46] and [47]. Ensuring the accuracy and reliability of the gathered data is a crucial factor when collecting data.…”
Section: A Data Collectionmentioning
confidence: 99%
“…To ensure that all targeted students have experience dealing with the E-Learning platforms, the data collection process was conducted after 2021, guaranteeing students' experience using E-Learning platforms. In the latter half of 2020, an entire shift in e-learning was implemented in both countries [46] and [47]. Ensuring the accuracy and reliability of the gathered data is a crucial factor when collecting data.…”
Section: A Data Collectionmentioning
confidence: 99%
“…The moderator of the model is Task Technology Fit. Though accuracy and self-efficacy were less significant, students loved e-learning [23]. The other study's results showed that (Perceived Ease of Use) plays a clear role in accepting e-learning and positively affects the acceptance rate (Perceived Usefulness), confirming that an information system can easily meet students' needs and convenience will be helpful for the student [24].…”
Section: Introductionmentioning
confidence: 97%